Thermal-flow patterns of m=1 in thermocapillary liquid bridges of high aspect ratio with free-surface heat transfer. (July 2021) - Fukuda, Yuya; Ogasawara, Toru; Fujimoto, Sorachi; Eguchi, Toshikazu; Motegi, Kosuke; Ueno, Ichiro
Highlights: Thermal-flow patterns of m = 1 in thermocapillary liquid bridges of high aspect ratio. Reproduce standing-wave-type oscillations that were observed more frequently in the microgravity experiments. 'x'-shaped structure of cold line of m = 1 over the free surface by higher azimuthal modal structures. Abstract: We investigate the thermal-flow patterns induced by the thermocapillary effect and their transition conditions in half-zone liquid bridges of high Prandtl number fluid; the effect of heat transfer between the liquid and the ambient gas through the liquid-bridge free surface is considered. We especially focus on the standing-wave-type oscillations after the transition onset, which were observed more frequently in the microgravity experiments (Matsugase et al., Int. J. Heat Mass Trans. (2015)) than the ground experiments, in a tall or high-aspect-ratio liquid bridge. We conduct a series of three-dimensional numerical simulations with the straight liquid bridge against a range of Biot number, and reproduce a pair of thermal waves of azimuthal wave number m = 1 propagating in opposite azimuthal directions under large Biot-number conditions by increasing the thermocapillary effect. Through a series of ground experiments with the liquid bridge exposed to the forced flow of the ambient gas, we illustrate the thermal-flow patterns of m = 1 and their transition conditions in terms of the Reynolds number for the forced flow of the ambient gas. We succeed in reproducing by both of experimental and numerical approaches the standing-wave-type oscillatory flows with 'x'-shaped low temperature bands on the free surface, which had been observed only in long-term microgravity experiments. We illustrate that the 'x'-shaped structure is realized by the higher azimuthal modal structures of the oscillatory convection.